2010
DOI: 10.1007/s00192-010-1211-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of transurethral injection of hyaluronic acid/dextranomer (NASHA/Dx gel) for the treatment of stress urinary incontinence (SUI)

Abstract: Transurethral injection of NASHA/Dx gel in women with SUI is associated with complications and not effective in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The findings are in good agreement with a study by Ghoniem et al that showed 88 % durability success and few complications after 2 years [27]. In contrast, two studies on transurethral injection of hyaluronic acid/dextranomer (NASHA/Dx gel) showed poor durability of effect and a high incidence of complications [28, 29]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings are in good agreement with a study by Ghoniem et al that showed 88 % durability success and few complications after 2 years [27]. In contrast, two studies on transurethral injection of hyaluronic acid/dextranomer (NASHA/Dx gel) showed poor durability of effect and a high incidence of complications [28, 29]. …”
Section: Discussionsupporting
confidence: 89%
“…Safety concerns have been raised regarding specific bulking agents because of migration, hypersensitivity, urethral erosion, pseudocysts/abscess, granuloma formation, and obstruction [39, 28, 29]. All AEs recorded after PAHG injection were generic and not related to the material.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of a periurethral bulking agent has also been associated with acceptably low rates of local complications, including transient hematuria, urinary retention, and irritative symptoms 28 . The limitation of current bulking agents is their lack of permanent durability, with the cure rate decreasing significantly over time, to about 30% at long‐term follow‐up 29–31 …”
Section: Surgical Management Of Failed Musmentioning
confidence: 99%
“…[1][2][3] New clinical applications are gaining interest, such as the use of soft tissue fillers for treating nonfacial areas, including glans penis augmentation, recurrent tracheoesophageal fistula, fecal incontinence, and stress urinary incontinence. [4][5][6][7] An ideal injectable soft tissue filler should guarantee safety including good biocompatibility, minimal risks of infection and rejection, risk of diffusion, lack of migration, and no carcinogenic potential. It should also be easily administered, long lasting, and inexpensive.…”
Section: Introductionmentioning
confidence: 99%